Calibration and experimental verification of discrete element parameters of Panax notoginseng root - Xie, Kaiting; Zhang, Zhaoguo; Wang, Fa’an; Yu, Xiaolan; Wang, Chenglin; Jiang, Shifei (International Journal of Agricultural and Biological Engineering, 2024)
Existing discrete element method-based simulation analysis of Panax notoginseng root soil separation still has the challenge to get the accurate and reliable basic parameters, which are necessary for discrete element simulation. In this paper, the P. notoginseng roots suitable for harvesting period were taken as the experimental object. Then using 3D scanning reverse modeling technology and EDEM software to establish the discrete element model of P. notoginseng, based on which, the physical and virtual tests were carried out to calibrate the simulation parameters. First, the basic physical parameters (density, triaxial geometric size, moisture content, shear modulus, and elastic modulus) and contact coefficients (static friction coefficient, rolling friction coefficient, and crash recovery coefficient between P. notoginseng roots and 65Mn steel) were measured by physical tests. Furthermore, treating the contact coefficients of P. notoginseng roots as the influence factor, the steepest uphill test, and four factors combing five levels of rotational virtual simulation are conducted. The measured relative error accumulation angle and simulation accumulation angle are set as the performance indices. The results show that the static friction coefficient, rolling friction coefficient, crash recovery coefficient, and surface energy coefficient of P. notoginseng roots are 0.55, 0.35, 0.16, and 19.5 J/m2, respectively. Using calibration results as parameters of the vibration separation simulation test of P. notoginseng soil, the Box-Behnken vibration separation simulation tests were carried out, in which the vibration frequency, inclination angle, and vibration amplitude of separation device as factors, screening rate and damage rate of P. notoginseng soil complex are regarded as indices. The results show that the optimal operating parameters of the separation device are the vibration frequency of 10 Hz, the inclination angle of 5°, and the amplitude of 6 cm. Based on the optimal operation parameters, the discrete element simulation experiment and field experiment of P. notoginseng roots soil separation are also performed to compare the soil three-dimensional trajectory space coordinates of P. notoginseng roots. From the results, three axis coordinate error is less than 15%. This proves that the calibration results are reliable. It can also provide the theoretical basis and technical support for the further study of the P. notoginseng root soil separation platform. Key words: Panax notoginseng; root; EDEM; parameter calibration; separation testDOI: 10.25165/j.ijabe.20241704.8122Citation: Xie K T, Zhang Z G, Wang F A, Yu X L, Wang C L, Jiang S F. Calibration and experimental verification of discreteelement parameters of Panax notoginseng root. Int J Agric & Biol Eng, 2024; 17(4): 13–23.